2012
DOI: 10.3109/09637486.2012.694848
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene content, antioxidant capacity and colour attributes of selected watermelon (Citrullus lanatus(Thunb.)Mansfeld) cultivars grown in India

Abstract: The present investigation reports variability in lycopene, ascorbic acid, total phenolics, antioxidant capacity and colour attributes of 12 watermelon cultivars grown in India. Antioxidant capacity was evaluated using four in vitro assays, namely ferric reducing antioxidant power, cupric reducing antioxidant capacity, Trolox equivalent antioxidant capacity and 2,2-diphenyl-1-picryl hydrazyl. Among watermelon cultivars, significant differences (p < 0.05) were found with respect to lycopene content and antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 18 publications
2
7
2
Order By: Relevance
“…Nagal et al. () examined the antioxidant capacities of 12 watermelon cultivars and reported that they ranged from 0.399 to 0.752 mmol TE/kg, which is only slightly higher than our value of 0.109 ± 0.090 mM TE.…”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation
“…Nagal et al. () examined the antioxidant capacities of 12 watermelon cultivars and reported that they ranged from 0.399 to 0.752 mmol TE/kg, which is only slightly higher than our value of 0.109 ± 0.090 mM TE.…”
Section: Resultscontrasting
confidence: 77%
“…The formulations with 0.04% EOC blend had higher antioxidant capacities than the other formulations, but they were not statistically significant from the other formulations. Nagal et al (2012) examined the antioxidant capacities of 12 watermelon cultivars and reported that they ranged from 0.399 to 0.752 mmol TE/kg, which is only slightly higher than our value of 0.109 ± 0.090 mM TE.…”
Section: Total Phenolic Content and Antioxidant Capacitycontrasting
confidence: 79%
“…For example, xanthophylls (lutein, violaxanthin and neoxanthin) are key components in light harvesting complexes (Woitsch and Römer 2003). Lycopene and β-carotene were found commonly to occur in chloroplasts and chloroplast, respectively, and to affect the color of some fruits and flowers (Jabeen et al 2013;Jarquín-Enríquez et al 2013;Nagal et al 2012). In recent years, carotenoids were also found to play important roles in various types of cleavage products in plants, bacteria, fungi, and animals (Heo et al 2013;Huang et al 2009;Ilg et al 2010;Liang et al 2011;Sui et al 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Perkins-Veazie et al (2016) found great variation in lycopene among 50 watermelon cultivars, ranging from 33 to 100 mg/kg. Yoo et al (2012) and Nagal et al (2012) both reported high variation in lycopene among cultigens.…”
Section: Discussionmentioning
confidence: 95%